Google Meeting Sebagai Media Alternatif di Masa Pandemi Dalam Pembelajaran Maharah Kitabah - Vinda (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2021)
During online learning, many applications have been launched to support the learning process in the world of education. Starting from the existence of the Learning Management System (LMS), the use of various kinds of Video Conferencing, even to the use of social media which is not a medium for learning but still used for the expected learning to take place. The research objective was to find out how to process and student’s responses related to the use of Video conferencing (Google Meet) in learning Khat Imla’ in the Arabic Language Education Department (PBA) in Semester II and IV of IAIN Surakarta. This type of research is qualitative with descriptive methods. The data collection techniques are interviews and questionnaires. The result of this study is the learning process using Google Meet video conferencing has been going quite well, seen from the level of student participation in attending lectures is very satisfying. In terms of understanding the material, it is quite understandable by students. However, from the point of view of using google meet to practice writing khat imla’, it is still less effective, due to signal problems which cause the video stucked when the lecture is practicing writing khat imla’, so that in the training and evaluation process there are still many students who complain of difficulties.